Somatic cell and factors which affect their count in milk - Zrinka Čačić; Samir Kalit; Neven Antunac; Mato Čačić (Mljekarstvo)
Milk quality is determined by chemical composition, physical characteristics and hygienic parameters. The main indicators of hygienic quality of milk are total number of microorganisms and somatic cell count (SCC.) Environmental factors have the greatest influence on increasing SCC. The most important environmental parameters are status of udder infection, age of cow, stage of lactation, number of lactation, breed, housing, geographicalarea and seasons, herd size, stress, heavy physical activity and, milking. A farmer (milk producer) himself can control a great number of environmental factors using good management practise and permanent education. Since SCC participate in creating the price of milk, it is necessary to inform milk producers how to organise their production so that they would produce maximum quantity of good hygienic quality milk.